HUBUNGAN PENGETAHUAN, SIKAP DAN TINDAKAN KELUARGA DENGAN GANGGUAN STRESS PADA PASIEN GANGGUAN JIWA DI POLI R.S. DR.ERNALDI BAHAR PALEMBANG TAHUN 2008 - Riza, Muchlis (Publikasi Penelitian Terapan dan Kebijakan, 2009)
Stress is respon body which is not specifik to body requirement annoyed, a universal phenomenon that happened in life one days and cannot refraining from, every people experiencing of it. Cause stress in general because of physical pressure existence, psikologis, and social. Departemental of health tell soul trouble amount in Indonesia reach 2,5 million people. This research aim for knowing relation of among knowledge, attitude, and the family action with occurrence stress, of at soul trouble patient in polyclinic of hospital dr. Ernaldi Bahar year 2008. This research using quantitative paradigma with the descriptive analysis. Sample is taken with technique accidental sampling that is family having family member suffering soul trouble which come medicinize in polyclinic of hospital dr. Ernaldi Bahar year 2008 amounting to 103 people.At this research is got by a relation existence of among family knowledge with occurrence stress (p value = 0,037), and got also the relation existence of between family attitude with occurrence stress (p value = 0,011). Besides that got also the relation existence of between family action with occurrence stress. (p value = 0,037). As for suggestion from researcher is namely expected from part of mental hospital perform effort of counselling to peoples of about stress and socialize more participating in improving knowledge, attitude, and action of family of about stress to minimize the happening of occurrence stress.